2021
DOI: 10.2478/orhu-2021-0014
|View full text |Cite
|
Sign up to set email alerts
|

Long-term lead intoxication of Griffon Vulture (Gyps fulvus Hablizl, 1783) supposedly the result of illegal shooting

Abstract: The European Griffon Vulture Gyps fulvus is a large-sized scavenger exploiting carcasses of livestock and wild ungulates and thus having a paramount importance in the natural ecosystems. In this study, we report on an adult Griffon Vulture detected with lead levels in the bones over the threshold. After two years of tracking, the bird died. The corpse’s clinical examination and radiography detected the presence of two embedded lead pellets from a healed gunshot wound in its right wing. Quantitative laboratory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…This concern is particularly heightened by the challenges associated with managing the usage of chronically toxic substances, which may inadvertently infiltrate human food sources. Furthermore, the prevalence of lead poisoning is widespread and can often be attributed to the illicit act of shooting in various geographical areas [11]. Due to the introduction of illicit projectiles into the animal's anatomy, it is commonly observed that the animal is struck and subsequently attempts to escape, only to endure a protracted period of lead toxicity, ultimately resulting in its demise.…”
Section: Human Influence and Harm To Vulturesmentioning
confidence: 99%
“…This concern is particularly heightened by the challenges associated with managing the usage of chronically toxic substances, which may inadvertently infiltrate human food sources. Furthermore, the prevalence of lead poisoning is widespread and can often be attributed to the illicit act of shooting in various geographical areas [11]. Due to the introduction of illicit projectiles into the animal's anatomy, it is commonly observed that the animal is struck and subsequently attempts to escape, only to endure a protracted period of lead toxicity, ultimately resulting in its demise.…”
Section: Human Influence and Harm To Vulturesmentioning
confidence: 99%